(untitled) (LACCEI, 2024)
The use of the online platform for educational services is essential for the achievement of academic objectives and goals, so that in the face of connectivity problems and lack of skills, these become a constraint to the teaching and learning process, causing stress, anxiety, anguish and other emotional problems in the student. The objective of this research is to determine the relationship between the use of the online platform and academic stress in secondary school students in Jaen (Cajamarca, Peru). The research has a quantitative approach, correlational level, non-experimental and cross-sectional design. The population consisted of a total of 120 high school students. Two questionnaires were used: one measuring the use of the online platform (in its three dimensions: use of didactic materials, classroom tutoring system and technological environment) and the other measuring academic stress (in its three dimensions: stressors, symptoms of stress and coping strategies). As result, we report that the use of online platform is high in 30.00% of the sample (n=120), medium in 60.83% and low in the remaining 9.17%. Similarly, academic stress is high in 30.00% of the sample, medium in 57.50% and low in the remaining 12.50%. Finally, there is significant relationship (positive and moderate) between the use of the online platform and academic stress (r=0.678).